Komunikasi Verbal dan Nonverbal dalam Penjualan Produk Dana Usaha Organisasi Mahasiswa Fakultas Ilmu Administrasi Universitas Brawijaya - aulia, Fara Ika (Universitas Brawijaya, 2024)
This research discusses the role of verbal and nonverbal communication in the sale of student organization business fund products. Student organizations often hold business fund product sales activities to raise funds. The success of business fund product sales depends on the ability of sellers to communicate with potential buyers. This study aims to identify the role of verbal and nonverbal communication in achieving the success of business fund sales by student organizations. The research method applied was qualitative, with data collection techniques involving observation and interviews. The results showed that verbal and nonverbal communication played an important role in the process of selling business fund products by student organizations of the Faculty of Administrative Sciences. Verbal communication becomes the main means to explain product features in detail, offer the benefits that the product has, and provide clear and informative responses to buyers' questions. Meanwhile, nonverbal communication, through friendly facial expressions, eye contact, and body movements that show confidence, plays a role in reinforcing messages and building positive relationships with buyers